2020
DOI: 10.2147/jaa.s262088
|View full text |Cite
|
Sign up to set email alerts
|

<p>Minimizing the Number of Aeroallergen Extracts in Skin Prick Test in IgE-Mediated Allergic Disorders in Both Adults and Children in Jordan</p>

Abstract: Background Skin prick test (SPT) is the most common diagnostic procedure that is performed considering the history of aeroallergen sensitivity among patients. Moreover, it is important to identify the diagnostic and therapeutic benefits of allergen’s number in skin prick testing in both adults and children. Objective The present study aims to detect the minimum number of allergens used in SPT to identify 95% of sensitized patients in both pediatric and adult age groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…In the present study, we identified eight allergens ( Dermatophagoides pteronyssinus , Dermatophagoides farinae , German cockroach, American cockroach, cat, Acacia , Bermuda grass, and careless weed) that were sufficient to identify 99–100% of sensitized children under 18 years of age with symptoms suggestive of allergic rhinitis or asthma or both. Our results were consistent with previous studies that found only eight to nine allergens were sufficient to identify allergen sensitization in children [ 16 18 ]. However, the types of allergens were different in different countries and geographies [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we identified eight allergens ( Dermatophagoides pteronyssinus , Dermatophagoides farinae , German cockroach, American cockroach, cat, Acacia , Bermuda grass, and careless weed) that were sufficient to identify 99–100% of sensitized children under 18 years of age with symptoms suggestive of allergic rhinitis or asthma or both. Our results were consistent with previous studies that found only eight to nine allergens were sufficient to identify allergen sensitization in children [ 16 18 ]. However, the types of allergens were different in different countries and geographies [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…A recent study from Jordan reported only eight allergen extracts were necessary to identify 95% of the sensitized patients. The eight allergen extracts used in children with allergic rhinitis or asthma or both were olive pollen, Dermatophagoides pteronyssinus , Salsola kali , cereals, wall pellitory, Dermatophagoides farinae , cypress, and Alternaria [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we identified eight allergens (Dermatophagoides pteronyssinus, Dermatophagoides farinae, German cockroach, American cockroach, cat, Acacia, Bermuda grass, and careless weed) that were sufficient to identify 99-100% of sensitized children under 18 years of age with symptoms suggestive of allergic rhinitis or asthma or both. Our results were consistent with previous studies that found only eight to nine allergens were sufficient to identify allergen sensitization in children [16][17][18]. However, the types of allergens were different in different countries and geographies [19].…”
Section: Discussionsupporting
confidence: 92%